Quantum Phases of Time Order in Many-Body Ground States - Guo, Tie-Cheng; You, Li (Frontiers in Physics, 2022)
Understanding phases of matter is of both fundamental and practical importance. Prior to the widespread appreciation and acceptance of topological order, the paradigm of spontaneous symmetry breaking, formulated along the Landau–Ginzburg–Wilson (LGW) dogma, is central to understanding phases associated with order parameters of distinct symmetries and transitions between phases. This work proposes to identify ground-state phases of the quantum many-body system in terms of time order, which is operationally defined by the appearance of the non-trivial temporal structure in the two-time auto-correlation function of a symmetry operator (order parameter) while the system approaches thermodynamic limit. As a special case, the (symmetry protected) time crystalline order phase detects continuous time crystal (CTC). We originally discover the physical meaning of CTC’s characteristic period and amplitude. Time order phase diagrams for spin-1 atomic Bose–Einstein condensate (BEC) and quantum Rabi model are fully worked out. In addition to time-crystalline order, the intriguing phase of time-functional order is discussed in two non-Hermitian interacting spin models.